Migration-Trust Networks : Social Cohesion in Mexican US-Bound Emigration - Flores-Yeffal, Nadia Yamel (Book collections on Project MUSE., 2013)
In a new application of sociological theories, the author offers fresh insights into the ways in which social networks function among immigrants who arrive in the United States from Mexico without legal documentation. She asks and examines important questions about the commonalities and differences in networks for this group compared with other immigrants, and she identifies "trust" as a major component of networking among those who have little - if any - legal protection. Revealing the complexities behind social networks of international migration, this book provides an empirical and theoretical analysis of how social networks of international migration operate in the transnational context. Further, the book clarifies how networking creates chain migration effects observable throughout history.